2008
DOI: 10.1073/pnas.0805802105
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive therapy mitigates immunological rejection of human embryonic stem cell xenografts

Abstract: Given their self-renewing and pluripotent capabilities, human embryonic stem cells (hESCs) are well poised as a cellular source for tissue regeneration therapy. However, the host immune response against transplanted hESCs is not well characterized. In fact, controversy remains as to whether hESCs have immune-privileged properties. To address this issue, we used in vivo bioluminescent imaging to track the fate of transplanted hESCs stably transduced with a double-fusion reporter gene consisting of firefly lucif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
221
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(234 citation statements)
references
References 33 publications
12
221
0
1
Order By: Relevance
“…In the last 10 years, more by injection of human peripheral blood leukocytes (13). In contrast, it was reported that hESCs transplanted into than 400 hESC lines have been established and studied worldwide (International stem cell registry, University immunocompetent mice were effectively recognized and rejected by the adaptive murine immune system (62 colony was cultured and mechanically dissected into small clumps every 5-6 days. ES cell colonies were culWe successfully determined the ABO genotypes of all hESC lines and obtained HLA-A, -B, -C, and -DR genotured in DMEM/F12 medium supplemented with 20% Knockout SR, 0.1 mM β-mercaptoethanol, 1% nonestype results from 27 of the 29 lines; the exceptions were two hESC lines that showed chromosomal triploidy/tetsential amino acids, 100 U/ml penicillin, 100 µg/ml streptomycin, and 4 ng/ml basic fibroblast growth factor raploidy, and HLA-A, -C, and -DR results were obtained in one of these two cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, more by injection of human peripheral blood leukocytes (13). In contrast, it was reported that hESCs transplanted into than 400 hESC lines have been established and studied worldwide (International stem cell registry, University immunocompetent mice were effectively recognized and rejected by the adaptive murine immune system (62 colony was cultured and mechanically dissected into small clumps every 5-6 days. ES cell colonies were culWe successfully determined the ABO genotypes of all hESC lines and obtained HLA-A, -B, -C, and -DR genotured in DMEM/F12 medium supplemented with 20% Knockout SR, 0.1 mM β-mercaptoethanol, 1% nonestype results from 27 of the 29 lines; the exceptions were two hESC lines that showed chromosomal triploidy/tetsential amino acids, 100 U/ml penicillin, 100 µg/ml streptomycin, and 4 ng/ml basic fibroblast growth factor raploidy, and HLA-A, -C, and -DR results were obtained in one of these two cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that human embryonic stem cells (hESCs) differentiate into osteogenic cells (6)(7)(8) and form compact bone tissue matrix when cultured on osteoconductive scaffolds in perfusion bioreactors (9). However, ethical controversy and concerns regarding immune properties of hESCs in allogeneic conditions hinder their clinical translation (10). Human-induced pluripotent stem cells (hiPSCs) reprogrammed using nonintegrating vectors (11,12) have the potential to overcome both limitations and be used to give rise to the cells of bone, vasculature, and adjacent tissues and to engineer autologous bone substitutes.…”
mentioning
confidence: 99%
“…Although other groups reported minimal or no immunogenicity of mouse syngenic iPSC lines and their cellular derivatives (15)(16)(17), these reports highlighted the need for an in-depth characterization of the inherent immunogenicity of hPSC. hESC lines express low levels of MHC class I molecules (18), exhibit immune-privileged properties (19,20), and are rejected in immune-competent mice through a T cellmediated allograft-rejection process (19,21,22); however, the inherent immunogenicity of human iPSC lines has not been examined carefully. In this article, we show that the terminally differentiated gold standard for human immunogenic cells, DC, can be successfully dedifferentiated into the iPSC state using Sendai virus, a nonintegrating RNA virus.…”
mentioning
confidence: 99%